The road to abolition?: the future of capital punishment in the United States - Ogletree, Charles J.; Sarat, Austin (The Charles Hamilton Houston Institute series on race and justice)
Introduction : toward and beyond the abolition of capital punishment / Charles Ogletree and Austin Sarat. Pt. I. Assessing the prospects for abolition. The executioner's waning defenses : the eroding defense of the executioner / Michael L. Radelet -- Blinded by science on the road to abolition? / Simon A. Cole and Jay D. Aronson -- Abolition in the U.S.A. by 2050 : on political capital and ordinary acts of resistance / Bernard E. Harcourt -- The beginning of the end? / Carol S. Steiker and Jordan M. Steiker -- Rocked but still rolling : the enduring institution of capital punishment in historical and comparative perspective / Michael McCann and David T. Johnson -- Pt. II. For execution methods challenges, the road to abolition is paved with paradox. For execution methods challenges, the road to abolition is paved with paradox / Deborah W. Denno -- Perfect execution : abolitionism and the paradox of lethal injection / Timothy V. Kaufman-Osborn -- No improvement over electrocution or even a bullet? : lethal injection and the meaning of speed and reliability in the modern execution process / Jürgen Martschukat -- Pt. III. Putting the death penalty in context. Torture, war, and capital punishment : linkages and missed connections / Robin Wagner-Pacifici -- Making difference : modernity and the political dimensions of death / Peter Fitzpatrick